Aerobic Fitness Affects the Exercise Performance Responses to Nitrate Supplementation. Issue 8 (August 2015) - PORCELLI, SIMONE; RAMAGLIA, MATTHEW; BELLISTRI, GIUSEPPE; PAVEI, GASPARE; PUGLIESE, LORENZO; MONTORSI, MICHELA; RASICA, LETIZIA; MARZORATI, MAURO
ABSTRACT: Purpose: Dietary nitrate supplementation has been shown to reduce O2 cost of submaximal exercise, improve exercise tolerance, and enhance performance in moderately trained individuals. In contrast, data have been provided that elite athletes do not benefit from nitrate supplementation. The aim of this study was to evaluate the effects of short-term nitrate supplementation on endurance performance in subjects with different levels of aerobic fitness. Methods: Twenty-one subjects (mean age, 22.7 ± 1.8 yr) with different aerobic fitness level (V˙O2peak value ranging from 28.2 to 81.7 mL·kg −1 ·min −1 ) participated in a crossover double-blind placebo-controlled study. Subjects were tested after 6 d of supplementation with either 0.5 l per day of nitrate (5.5 mmol)-containing water (NITR) or nitrate-free water (PLA). Participants performed an incremental running test until exhaustion and four repetitions of 6-min submaximal (approximately 80% of gas exchange threshold) constant load exercise on a motorized treadmill. Moreover, subjects performed a 3-km running time trial on the field. Results: After NITR, a negative correlation between reduction of O2 cost of submaximal exercise and individual aerobic fitness level was observed ( r 2 = 0.80; P < 0.0001). A significant inverse correlation was also found between aerobic fitness level and improvement in performance for 3-km time trial after NITR ( r 2 = 0.76; P < 0.0001). Additionally, subjects responded differently to dietary nitrate supplementation according to aerobic fitness level with higher-fit subjects showing a lower increase in plasma [NO3 − ] ( r 2 = 0.86; P < 0.0001) and [NO2 − ] ( r 2 = 0.75; P < 0.0001). Conclusions: The results of the present study suggest that the individual aerobic fitness level affects the ergogenic benefits induced by dietary nitrate supplementation. The optimal nitrate loading regimen required to elevate plasma [NO2 − ] and to enhance performance in elite athletes is different from that of low-fit subjects and requires further studies.